Development and Characterization of Advanced Recycled Hybrid Metal Matrix Composites via Enhanced Stir Squeeze Casting Method for Industrial Applications - Unegbu, Hyginus Chidiebere Onyekachi; Yawas, Danjuma S. (JURNAL MECHANICAL, 2024)
This study presents the development and characterization of advanced recycled hybrid metal matrix composites (HMMCs) using an optimized stir squeeze casting technique. The hybrid composites were fabricated using recycled aluminum alloy (AA6061), ceramic particles, and carbon fibers. The optimization of critical process parameters such as stirring speed, casting temperature, and squeeze pressure resulted in composites with superior mechanical and physical properties. Comprehensive testing revealed that the HMMCs exhibited a 20% increase in tensile strength, a 30% improvement in hardness, and a 15% enhancement in impact resistance compared to conventional metal matrix composites (MMCs). Additionally, the composites demonstrated a 10% improvement in thermal conductivity, making them suitable for applications requiring efficient heat dissipation. The successful incorporation of recycled materials not only promoted sustainability but also reduced production costs. The findings underscore the potential of these hybrid composites for high-performance applications in automotive, aerospace, and thermal management industries. Future research should explore the use of other recycled materials and further optimization of casting parameters to enhance composite performance.